Estimativa da incerteza na determinação da área do fotopico gama 186 keV em espectros de urânio com alta resolução - Dias, Fábio Cordeiro (2017)
Non-destructive uranium enrichment determination by gamma-ray spectrometry is widely used at nuclear facilities, laboratories and other institutions as a tool to quantify and control processed and/or stored 235U inventories. In nuclear safeguards, this technique is very useful, since 235U has a high strategic value and non-destructive techniques have the capability to provide measurement results in a quick way. The enrichment determination depends primarily on the quantification of areas of gammarays emitted by uranium, in particular the 185.7 keV peak from 235U. As a result, the estimation of the uncertainty associated with the peak area is critical for achieving reliable enrichment results. The main methods for peak area determination were experimentally tested in regards to uncertainty estimation. It was observed they are subject to significant correlations between input quantities. For achieving adequate estimates, the user must assure that correlations are properly quantified; otherwise the process of evaluating and accepting measurement results may be seriously compromised. The selection of the most adequate measurement method for a specific application must take that fact into consideration.